A Review on Factors Effecting The adsorption of Heavy Metal Using Different Biosorbents - Salih, Suha (Anbar Journal of Engineering Sciences, 2024)
Agricultural, industrial, and household debris can be employed as biosorbents to extract heavy metals from water that has been contaminated. Kitchen waste includes, among other things, peels from promotional gates, lemons, avocados, apples, kiwis, watermelons, and onions. Moreover, coffee and tea grounds are considered to be household refuse. This review illustrates the scholarly investigations that explored the potential of various waste materials as adsorbents for wastewater treatment. An extensive array of experiments was conducted to determine the variables that influence the capacity of these materials to adsorb heavy metals. To undertake the experiments above, different concentrations of biosorbent were introduced into the effluent at various contact times and pH levels. The researchers investigated the effects of varying these parameters and found that the biosorbent’s ability to adsorb heavy metals is directly proportional to these factors. The results and conclusion indicated that the impact of biosorbent concentration and contact duration on the pH of contaminated water was assessed. To encourage the incorporation of industrial, agricultural, and household refuse into water treatment processes rather than permitting it to accumulate as an environmental hazard.